Analysis of the special features of the thermal process in an induction generator at high saturation of the magnetic system - Chenchevoi, V.; Romashykhin, Iu; Romashykhina, Zh.; Al-Mashakbeh, Atef S. (Електротехніка і електромеханіка, 2017)
Purpose. Development of the method for the assessment of the thermal operation modes of an autonomous electrical power system with an induction motor, aiming at improvement of the reliability of electricity supply and the quality of electric energy. Methodology. Induction generator mathematical modeling taking into account the magnetic system saturation was used in the research. A heat model taking into account the excess of the temperature of the induction generator units in the mode of high saturation was developed. The obtained results were compared with the experimental data. Results. The paper contains the solution to the problem of improvement of the mathematical model sand methods for steel losses determination in there search of the operation modes of an autonomous uncontrolled induction generator taking into consideration the properties of the magnetic system in the mode of high saturation. The expression for determination of steel losses in the mode of high saturation is obtained. It enables the assessment of the induction generator thermal condition. Originality. The analytical dependence for the calculation of the steel losses in the mode of magnetic system saturation has been obtained for the first time. Practical value. The obtained expression for the calculation of the steel losses can be used for determination of the admissible time of generator operation at overload. It will allow avoiding broken winding insulation and complete use of the generator overload capacity. As a result, it will reduce possible irregularities of electricity supply due to the generator preliminary cutoff